Marketing Strategy Implementation for Business Plan at Imported Beef Supply Startup Meat Tech - Fetiana Pristianti; Tantri Yanuar Rahmat Syah; Unggul Kustiawan; Nofierni Nofierni (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The culinary industry in Indonesia, especially among the middle class in major cities such as Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek), is experiencing rapid growth. To continue attracting consumer interest, restaurants compete to introduce new and unique menus. This presents an opportunity for suppliers like PT Meat Tech, which specializes in providing high-quality imported beef, to innovate and meet market demand. A marketing plan is a strategic process in marketing that aims to achieve predetermined targets. In this process, the marketing strategy is a crucial element as it encompasses the company’s values and objectives. PT Meat Tech will focus on Marketing Goals and Objectives, Segmentation, Targeting, and Positioning (STP) Strategy, business-to-business (B2B) Marketing Mix, Sales Activities, Sales Budget Projections, and Revenue Stream Projections to enhance sales and achieve revenue targets. This study aims to assist PT Meat Tech in successfully marketing its beef products through differentiation strategies that support revenue growth. Data collection will involve a multifaceted approach, including semi-structured interviews with key stakeholders at Meat Tech, such as marketing managers, sales representatives, and other relevant personnel. The study results indicate that an effective marketing plan is influenced by several factors, including the business establishment purpose, pricing strategy, location, promotion, sales activities, and financial management. By addressing these factors, PT Meat Tech can optimize its marketing strategy and strengthen its market position.